2019
DOI: 10.1002/jsfa.9700
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cadmium in bread and biscuit samples using ultrasound‐assisted temperature‐controlled ionic liquid microextraction

Abstract: BACKGROUND In the present work, a simple and rapid method was proposed for the preconcentration of cadmium using ultrasound‐assisted temperature‐controlled ionic liquid microextraction (TC‐IL‐LPME). The dispersion of the ionic liquid (1‐Hmim[PF6]) in the aqueous phase was performed by heating it in an ultrasonic bath, followed by cooling in an ice bath. After centrifugation, the enriched phase was dissolved in 45% (w/w) nitric acid solution to reduce viscosity, and the cadmium content was measured employing el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The safety characteristics of raw materials in terms of heavy metals are ruled by current legislation and rely on continuous analytical monitoring. Recently, a cheap, rapid, and ecological method was proposed for the preconcentration of cadmium in biscuit samples by using ultrasound-assisted temperature-controlled ionic liquid microextraction (TC-IL-LPME), making analyses easier [42].…”
Section: Chemical Contaminantsmentioning
confidence: 99%
“…The safety characteristics of raw materials in terms of heavy metals are ruled by current legislation and rely on continuous analytical monitoring. Recently, a cheap, rapid, and ecological method was proposed for the preconcentration of cadmium in biscuit samples by using ultrasound-assisted temperature-controlled ionic liquid microextraction (TC-IL-LPME), making analyses easier [42].…”
Section: Chemical Contaminantsmentioning
confidence: 99%
“…Determination of Cd in fish by atomic absorption spectrometry with electrothermal atomization is based on sample digestion in a microwave oven and subsequently read using an atomic absorption spectrometer with a graphite furnace (Costa et al, 2012 ). Determination of Cd in bread and biscuit samples using ultrasound-assisted temperature-controlled ionic liquid microextraction is presented as a simple, cheap, ecological, and sensitive alternative (Santos et al, 2019 ). An all-solid light addressable potentiometric sensor (LAPS) is presented for determination of Cd in rice, which is satisfactory precision, accuracy, and selectivity (Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ionic liquids (ILs) have become promising alternatives to the traditional organic solvents employed in sample preparation because of their unique properties, such as negligible vapor pressure, high thermal stability, non-flammability and good solubility for many inorganic and organic compounds [17]. Therefore, ILs have been extensively applied as substituents for conventional organic solvents in various extraction processes including salt-induced liquid-liquid extraction (SI-LLE) [18], dispersive liquid-phase microextraction (DLPME) [19], microwave-assisted extraction (MAE) [20], pressurized liquid extraction [21], ultrasonic-assisted extraction [22][23][24] and temperature-controlled liquid phase micro-extraction (TC-LPME) [25][26][27][28]. In this context, hydrophobic ILs are usually used to extract liquid samples, while hydrophilic ILs are mostly used to extract solid samples.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high viscosity of hydrophobic ILs and the difficulty of phase separation, it is rarely reported that hydrophobic ILs were directly used to extract solid samples [29]. In most cases, water and organic solvent were firstly used to extract the trace components in solid samples, and then hydrophobic ILs were selected to extract and concentrate the trace components in the extracts [25]. This process was not only complicated and time-consuming, but also easy to cause measurement errors.…”
Section: Introductionmentioning
confidence: 99%